Cope-type Hydroamination of Alkenes with Hydroxylamines and Hydrazines - Scope and Mechanism - Loiseau, Francis (Université d'Ottawa / University of Ottawa, 2013)
Hydroamination stands as a desirable approach to nitrogen-containing molecules, which have important applications ranging from pharmaceuticals (fine chemicals) to paints, coatings, insecticides and agrochemicals (bulk chemicals). It features the use of alkene and alkyne starting materials, which are abundant and rarely used in the formation of C-N bonds. This work aims at building on the improved Cope-type reactivity developed in the Beauchemin group by expanding the reach of the reaction and understanding its mechanistic complexities. The first part of this thesis describes the development of cascade reactions to provide a thermodynamic driving force for the intermolecular Cope-type hydroamination of alkenes. The methodology serves as a proof of concept that the dipolar reaction intermediates can be engineered to further react irreversibly to more stable products, and has shown potential in improving the syntheses of natural alkaloids. The second part of the thesis describes the expansion of Cope-type hydrazide hydroaminations through a systematic investigation of hydrazine analogs as reactants. Optimized reagents are featured in the first reported intermolecular Cope-type hydrohydrazidation of alkenes. Mechanistic investigations and isolation of ammonium ylide intermediates support a 5-membered concerted and planar mechanistic pathway for hydrazide hydroaminations, similar to that observed with hydroxylamines. The final section presents mechanistic data disproving a previously assumed difficult proton transfer step in the hydroamination using hydroxylamines. From such findings, early results are presented towards a hydrogen-bond catalyzed hydroamination, which has potential applicability across the field of Cope-type hydroaminations and beyond.
Keywords: Synthesis; Hydroamination; Hydrohydrazination; Hydroxylamine; Hydrazine; Catalysis; Nitrogen; Cascade Reactions; Alkaloids